The Dynamics of Somatic Exocytosis in Monoaminergic Neurons - Sarkar, Bidyut; Das, Anand K.; Arumugam, Senthil; Kaushalya, Sanjeev K.; Bandyopadhyay, Arkarup; Balaji, Jayaprakash; Maiti, Sudipta (Frontiers in Physiology, 2012)
Some monoaminergic neurons can release neurotransmitters by exocytosis from their cell bodies. The amount of monoamine released by somatic exocytosis can be comparable to that released by synaptic exocytosis, though neither the underlying mechanisms nor the functional significance of somatic exocytosis are well understood. A detailed examination of these characteristics may provide new routes for therapeutic intervention in mood disorders, substance addiction, and neurodegenerative diseases. The relatively large size of the cell body provides a unique opportunity to understand the mechanism of this mode of neuronal exocytosis in microscopic detail. Here we used three photon and total internal reflection fluorescence microscopy to focus on the dynamics of the pre-exocytotic events and explore the nature of somatic vesicle storage, transport and docking at the membrane of serotonergic neurons from raphe nuclei of the rat brain. We find that the vesicles (or unresolved vesicular clusters) are quiescent (mean square displacement, MSD ~0.04 μm²/s) before depolarization, and they move minimally (< 1 μm) from their locations over a time scale of minutes. However, within minutes of depolarization, the vesicles become more dynamic (MSD ~0.3 μm²/s), and display larger range (several μm) motions, though without any clear directionality. Docking and subsequent exocytosis at the membrane happen at a timescale (~25 ms) that is slower than most synaptic exocytosis processes, but faster than almost all somatic exocytosis processes observed in endocrine cells. We conclude that, A) depolarization causes de-tethering of the neurotransmitter vesicles from their storage locations, and this constitutes a critical event in somatic exocytosis; B) their subsequent transport kinetics can be described by a process of constrained diffusion, and C) the pre-exocytosis kinetics at the membrane is faster than most other somatic exocytosis processes reported so far.